2018
DOI: 10.7150/thno.23632
|View full text |Cite
|
Sign up to set email alerts
|

Imaging, myeloid precursor immortalization, and genome editing for defining mechanisms of leukocyte recruitment in vivo

Abstract: Recruitment of leukocytes from the blood to sites of inflammation poses a promising target for new diagnostic and therapeutic approaches. We aimed to develop a novel method to non-invasively analyze molecular mechanisms of leukocyte migration in pre-clinical models of inflammation in vivo.Methods: We used the ER-HoxB8 system to transiently immortalize murine myeloid precursors from wildtype and CD18- as well as MRP14-deficient mice. A VLA4α-/- cell line was generated by CRISPR/Cas9-mediated gene editing. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…Myh9‐deficient NLC had severe migration defects in 2D and 3D environments that were restored by viral transduction of EGFP‐Myh9, further validating the use of this cellular model for critical rescue experiments. Two other studies showed that dye‐labeled HoxB8‐derived cells injected intravenously are recovered at inflammatory sites, validating the use of HoxB8‐derived neutrophils for adoptive transfer experiments. The Mc Donald et al.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Myh9‐deficient NLC had severe migration defects in 2D and 3D environments that were restored by viral transduction of EGFP‐Myh9, further validating the use of this cellular model for critical rescue experiments. Two other studies showed that dye‐labeled HoxB8‐derived cells injected intravenously are recovered at inflammatory sites, validating the use of HoxB8‐derived neutrophils for adoptive transfer experiments. The Mc Donald et al.…”
Section: Discussionmentioning
confidence: 81%
“…The HoxB8 system was recently used to establish the role of the non‐muscle myosin Myh9 in neutrophil trafficking in vitro and to monitor neutrophil trafficking during inflammation in vivo . These studies validate the use of this cellular model to study neutrophil trafficking in vitro and in vivo and highlight its advantages for rescue experiments or adoptive transfer of cells bearing mutations resulting in lethal phenotypes in mice.…”
Section: Introductionmentioning
confidence: 78%
“…. Moreover, the assay is suitable for mouse bone marrow-derived macrophages or macrophages derived from conditionally immortalized myeloid precursor cells 39,40 . We have previously used polytetrafluoroethylene (PTFE) bags with luer adapters to culture bone marrow cells and obtain macrophages…”
mentioning
confidence: 99%
“…This could allow to define the macrophage migration mode within a large collection of healthy or pathological tissues isolated from different mouse models. The use of ER-Hoxb8 monocytes injected in blood circulation to study tissue recruitment of leukocytes from blood has been recently described (Gran et al, 2018). A future objective will be to examine by intravital microscopy the migration of macrophages in tumors (Gui et al, 2018) by labeling genetically modified Hoxb8-macrophages and directly injecting them within tumors generated in dorsal window chambers.…”
Section: Discussionmentioning
confidence: 99%